A Case Report of Chlamydia psittaci Infective Endocarditis Complicated With Pneumonia - Dongmei Zhao; Li Zhang; Qiulin Sun; Jun Cheng (Case Reports in Infectious Diseases)
Psittacosis is a zoonotic disease caused by Chlamydia psittaci and is commonly found in birds and poultry. Human infection is uncommon, and most cases are sporadic. Infection of extrapulmonary organs by Chlamydia psittaci is extremely rare. A rare case of infective endocarditis complicated by pneumonia caused by Chlamydia psittaci was reported, which was diagnosed using metagenomic next-generation sequencing (mNGS). The patient recovered after receiving appropriate anti-infective treatment. Discussion on the pathogenesis, diagnosis, and treatment of this disease based on recent literature reports aimed to improve the prognosis of similar patients and enhance the understanding of clinicians.